Epidemiology of Childhood Intussusception and Determinants of Recurrence and Operation: Analysis of National Health Insurance Data Between 1998 and 2007 in Taiwan - Solomon Chih-Cheng Chen; Jung-Der Wang; Hong-Yuan Hsu; Mee-Mee Leong; Teck-Siang Tok; Yow-Yue Chin (Elsevier, 2010)
To study the epidemiology of childhood intussusception and risk factors of recurrence and operation based on a nationwide data. Methods: Children with hospitalization due to intussusception (ICD9: 560.0) between 1998 and 2007 were identified from a national health insurance database. The incidence was calculated by age, sex, calendar year and month of admission. Recurrence and operation rates, duration and costs of hospitalization were analyzed. Results: A total of 8217 intussusception-related hospitalizations were identified in 7541 children. The incidence of intussusception peaked between 3 and 36 months of age. Male -to-female incidence rate ratio increased from 1.31 in the first year to 2.52 in the ninth year of life. The overall recurrence and operation rates were 7.9% and 24.9%, respectively. In children less than 1 year old, the recurrence rate was 10.1%, which decreased to 5.3% in children over 3 years old. Multiple logistic regression analysis showed that children receiving operation had a significantly lower risk of recurrence with an odds ratio (95% confidence interval) of 0.31 (0.24-0.41) after controlling for age and sex. There are significantly more cases occurring during the warmer months between May and October compared to the cooler months between November and April. Conclusions: There was a male predominance of intussusception with a dynamic male-to-female incidence rate ratio. Children under 1 year of age have the highest recurrence and operation rates. Seasonal variation of intussusception was suspected in Taiwan.